Pediatric Kidney Transplantation: Frameshift in Medical and Surgical Management. Does the Perioperative Setting Have an Impact on Transplant Outcome? A Single-Center Experience - Bergel, Berenice; Geppert, Tamara; Bañuelos Marco, Beatriz; Friedersdorff, Frank; Müller, Dominik; Kempf, Caroline; Lachmann, Nils; Lingnau, Anja (Frontiers in Surgery, 2022)
Introduction Frameshift in medical management as well as in surgical thinking is putting the patient as a whole is the focus, rather than just the disease. To optimize the treatment of our pediatric transplant patients in our institution, we changed in 2013 the transplant program setting, treating and operating all pediatric transplant patients exclusively in a pediatric environement. The aim of this study was to analyze whether or not this change had an impact on patients safety, patient population and patients and transplant outcome. Methods In the retrospective analysis, we compared transplant outcome of two eras. Era1 (2008-2012) solely included patients treated in the adult facilities, era2 (2013-2017) patients were exclusively treated in the pediatric environment. Results Included were 53 renal transplant patients, era1 (28 patients) and era2 (25 patients). Overall mortality was 5.6%. Median recipient age at transplantation was 13.2 years in era1 and 8.59 years in era2, median recipient weight at transplantation was 41.7 kg in era1 vs 26 kg in era2, median size 149. 5 cm (era1) vs. 123 cm in era2 (p=0.05). The direct recipient/donor weight ratio remained stable in both eras, for recipients below 20 kg we saw a larger weight mismatch in era1 (0.84 vs 0.66). In the subgroup of CAKUT patients (congenital anomalies of the kidney and urinary tract) those were significantly younger at onset of dialysis (p<0.001) and at time of transplantation (p<0.001), also they were less in body weight (p<0.01) and body size (p<0.001), this subgroup war larger in era2. HLA mismatch data, serum creatinine and GFR yield comparable results in both groups. Median time to detection of DSA was 46.2 month (3.8 years). Conclusion Since children with end stage renal disease at time of transplant trend to be younger and smaller, it is crucial to ensure a medical environment that is able to address their particular challenges. Even in this recipient cohort, renal transplantation can be performed safely as outlined by our data.